MANTRA MELAYU KETAPANG DALAM DIALEKTIKA DAKWAH ISLAMIYAH DAN BUDAYA LOKAL - Zaenuddin Hudi Prasojo; Putri Wulansari (INSTITUT AGAMA ISLAM NEGERI PONTIANAK, 2020)
This article examines the use of mantra as a form of local wisdom within Ketapang Malay community. Meaning of mantra is found in the practices of daily life in the community. To explore the meaning, this work begins with analyzing the description of the form of mantra and its structure normally found in the Ketapang Malay community. Employing qualitative analysis, this paper presents the relevance of mantra as a form of local wisdom in its dialectic with the development of Islam within the Ketapang Malay community. The results of the analysis show that the mantra tradition in the Ketapang Malay community is apart of an oral tradition that has long been practiced before Islam. Religioous values can be seen in the oral tradition of mantra used by the Malay people of Ketapang which exist to date. To a certain extent, this tradition of mantrafuctions as an alternative in accommodating the interests of the community in the frame of local wisdom. The use of mantra for various purposes is a portrait of people's life patterns of the Ketapang Malay people who still believe in magical powers in their religious practices. Keywords: Dialectic, mantra, Local Wisdom, Malay, Ketapang Artikel ini mengkaji tentang penggunaan mantra sebagai bentuk kearifan lokal masyarakat Melayu Ketapang. Pemaknaan mantra ditemukan dalam praktik kehidupan sehari-hari pada masyarakat Melayu di wilayah Ketapang ini. Untuk mendalami pemaknaan tersebut, artikel ini memulai dengan deskripsi bentuk mantra yang digunakan dan struktur mantra yang biasanya ditemui pada masyarakat Melayu Ketapang. Dengan analisis kualitatif, tulisan ini menyajikan relevansi mantra tersebut sebagai kearifan lokal dalam dialektikanya dengan perkembangan agama Islam pada masyarakat Melayu Ketapang.Hasil analisis menunjukkan bahwa tradisi mantra pada masyarakat Melayu Ketapang merupakan bagian dari tradisi lisan yang sejak lama telah dipraktikkan sebelum Islam.Unsur-unsur agama dapat dilihat pada tradisi lisan mantra yang digunakan oleh masyarakat melayu Ketapangyang eksis sampai saat ini.Dalam batas tertentu, tradisi mantra ini menjadi sebuah alternatif dalam mengakomodasi kepentingan-kepetingan masyarakat dalam bingkai kearifan lokal.Pemanfaatan mantra untuk beragam tujuan ini menjadi potret pola kehidupan masyarakat Melayu Ketapang yang masih mempercayai kekuatan magis dalam praktik keagamaannya. Kata Kunci: Dialektika, mantra, kearifan lokal, Melayu, Ketapang